Adsorption of mercuric ion from aqueous solutions using modified fly ash - Chinh, Nguyen Thuy; Trang, Tran Do Mai; Tuyet, Nguyen Thi; Oanh, Nguyen Nhat; Mai, Tran Thi; Thi Thu Trang, Nguyen; Hoang, Thai (Vietnam Journal of Science and Technology, 2018)
In this study, fly ash was treated with NaOH solution (FAN) before modifying with (3-mercaptopropyl) triethoxysilane - MPTMS (FAMPS). By using FTIR, FESEM, XRD, EDX, and BET techniques, the change in structure, composition and morphology of FAN and FAMPS was evaluated. The FTIR spectra of FAN and FAMPS showed that there is no chemical reaction between the MPTMS and FAN. After modification, the FAMPS has a rough surface with composition difference from the FAN. Mercuric ion adsorption behavior as well as adsorptionisotherm models (Langmuir and Freundlich) of the FAN and FAMPS were also investigated and discussed. Thanks to FAN modification, the mercuric ion removal percent of the FAMPS was higher than that of the FAN. Owing to the adsorption data, Freundlich isotherm modelwas fitted for the mercuric ion adsorption process.